2022
DOI: 10.1186/s13012-022-01248-x
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of implementation science outcomes in low- and middle-income countries: a scoping review

Abstract: Background Historically, the focus of cost-effectiveness analyses has been on the costs to operate and deliver interventions after their initial design and launch. The costs related to design and implementation of interventions have often been omitted. Ignoring these costs leads to an underestimation of the true price of interventions and biases economic analyses toward favoring new interventions. This is especially true in low- and middle-income countries (LMICs), where implementation may requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A recently published review detailed the dearth of economic analyses for implementation science research. There is very little published knowledge about implementation cost descriptions and outcomes [ 39 ]. Prior to this study, there has been little research or guidance for implementers on the initial investment costs needed to set up MWHs, or the costs per outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review detailed the dearth of economic analyses for implementation science research. There is very little published knowledge about implementation cost descriptions and outcomes [ 39 ]. Prior to this study, there has been little research or guidance for implementers on the initial investment costs needed to set up MWHs, or the costs per outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, frameworks developed for complex interventions have also not sufficiently addressed program cost estimation [ 17 – 20 ]. Methodological guidance is emerging for specific cost components, such as implementation costs of public health programs [ 21 , 22 ], but this cannot account for the full breadth of program costs of DHIs. Therefore, the existing scientific literature is insufficient to help standardize the estimation and reporting of program costs of DHIs.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare organizations are constantly using EBP to enhance the quality of care and improve patient outcomes (Lennox et al, 2018; Zhao et al, 2022). Nevertheless, a scoping review has pointed out that implementing improvements or innovations in low‐ and middle‐income countries requires a substantial investment of resources (Malhotra et al, 2022). Some studies have suggested that most improvements or innovations decline over time, resulting in wasted benefits including time and financial investment (Lennox et al, 2020; Proctor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%